Impact of salt erosion on mechanical and drying shrinkage performance of cement stabilized macadam - Wang, Chengbin; Chen, Yadi; An, Baoping; Guo, Qinglin; Wang, Yibo (Frontiers in Materials, 2024)
Abstract：The arch expansion damage of asphalt pavement is a typical disease in desert Gobi and saline-alkali areas, and the reasons for arch expansion are very complex. Exploring the impact of salt solution on the mechanical and drying shrinkage performances of cement-stabilized macadam helps to clarify the causes of the arch expansion damage. To this purpose, this paper designed a salt solution infiltration experiment, using salt solution infiltration to simulate the transmission and accumulation of salts in cement-stabilized macadam, and carried out the compressive and flexural tests of cement-stabilized mortar and cement-stabilized macadam, and measured the drying shrinkage performance of cement-stabilized mortar and macadam. The results show that the type of salt solution has a significant influence on the weight of the cement-stabilized mortar samples, sulfates will cause the samples to lose weight, while chlorides and mixed solutions cause the increase in weight. Chlorides and sulfates lead to the decrease in the strengths of cement-stabilized mortar and macadam. The salt crystallization will lead to the decline of the drying shrinkage strains of cement-stabilized mortar and macadam, which has a positive action for reducing the drying shrinkage deformation. However, under the combined action of chlorides and sulfates, cement-stabilized macadam expands with the moisture loss. This may be one of the important causes of the arch expansion of asphalt pavement in the Gobi area and saline-alkali area.